The fiscal cost of the provision of basic public services, subsidies for expenditure on food and basic citizen income per household during the COVID-19 pandemic: An expenditure analysis - Luis Miguel Galindo Paliza; Fernando Filgueira; Marike Blofield; Carlos Alberto Francisco Cruz (Latin American Economic Review, 2020)
The objective of this article is to estimate the fiscal costs, using income and expenditure surveys, of the provision of basic public services (electricity, water, telephone and internet) for the 40% of the population with the lowest incomes, the provision of a subsidy of 50% of actual food expenditure for the 40% of the population with the lowest incomes and the provision of a basic income per household equivalent to the value of the poverty line for households under the poverty line in Costa Rica, Guatemala and El Salvador during the COVID-19 pandemic. These fiscal options are a fundamental component of any public health strategy against the COVID-19 considering they give economic viability to the population during the isolation and mobility restrictions period and financial support during the economic and social emergency. The results show that the fiscal costs of the provision of basic public services to 40% of the population with the lowest incomes or other fiscal measures considering less ambitious targets are heterogeneous between these Central American countries because of previous conditions and public policies but are reasonable and possible to cover under the actual circumstances.
Keywords: E62; E63; 330; COVID-19; consumption; basic public services; food; basic income; fiscal costs